Leveraging natural variation to study fitness costs and trade-offs in host immunity - Ordovás-Montañés, M (2021)
During health and infection, hosts allocate energy to growth, maintenance, defense, and reproduction. Current theory in ecological immunology suggests that mounting an energetically-costly defense will lead to trade-offs against host fitness. In this thesis, we used lab-adapted and wild Caenorhabditis elegans as model hosts to directly test for fitness costs of immune-upregulation and pathogen damage, as well as trade-offs with reproduction, after transient exposure to an opportunistic pathogen, Staphylococcus aureus. Utilizing a spectrum of wild host genotypes allowed us to explore the breadth of genetic and functional variation for naturally-relevant alleles. We found that despite short-term delays in reproduction after S. aureus exposure, all host isolates recovered and had similar total brood sizes as nematodes fed only control bacterial food (Chapter 2). We subsequently examined the impact of pathogen exposure across several generations in population size assays. We found a genetic correlation across host isolates such that those with a relatively smaller population size after transient S. aureus exposure had relatively larger population sizes after exposure to a second opportunistic pathogen, Pseudomonas aeruginosa (Chapter 3). This finding suggests that C. elegans has ‘balanced immunity’ against these two distinct pathogen species, evidenced at the population level. Finally, we found no evidence of a beneficial pathogen-induced maternal effect but did identify that lab-adapted nematodes have the highest magnitude of cost from maternal pathogen exposure (Chapter 4) and this corresponds to the magnitude of the delay reported in Chapter 2. Surprisingly, our findings in genetically-diverse isolates identify trade-offs in pathogen-tailored defense strategies as more important drivers of population size than energy-based trade-offs from mounting an immune response or suffering pathogen damage. We discuss the potential of studying nematode-pathogen systems with more naturalistic conditions to address ecological immunology questions using naturally-derived isolates with ecologically-relevant parameters.